2019
DOI: 10.3390/s19132986
|View full text |Cite
|
Sign up to set email alerts
|

High Precision Compensation for a Total Reflection Prism Laser Gyro Bias in Consideration of High Frequency Oscillator Voltage

Abstract: Traditional compensation methods based on temperature-related parameters are not effective for complex total reflection prism laser gyro (TRPLG) bias variation. Because the high frequency oscillator voltage (UHFO) fundamentally affects the TRPLG bias, and the UHFO has a stronger correlation with the TRPLG bias when compared with the temperature, an introduction of UHFO into the TRPLG bias compensation can be evaluated. In consideration of the limitations of least squares (LS) regression and multivariate stepwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…is the frequency parameter of Ne 20 , ξ is the frequency parameter of Ne 22 , Z i is the imaginary part of plasma dispersion function. When F = 0.53, i.e., Ne 20 : Ne 22 = 53 : 47, a more symmetric double isotope gain curve can be obtained, as shown in Figure 2.…”
Section: Light Intensity Stabilization Principle Of Trplgmentioning
confidence: 99%
See 1 more Smart Citation
“…is the frequency parameter of Ne 20 , ξ is the frequency parameter of Ne 22 , Z i is the imaginary part of plasma dispersion function. When F = 0.53, i.e., Ne 20 : Ne 22 = 53 : 47, a more symmetric double isotope gain curve can be obtained, as shown in Figure 2.…”
Section: Light Intensity Stabilization Principle Of Trplgmentioning
confidence: 99%
“…Scale factor error refers to variations in the scale factor as a function of the rotation rate [17], [18]. Null shift happens when the frequency difference is nonzero for zero input rate, it can be corrected by temperature compensation techniques and other composite signals compensation techniques based on least squares support vector machine [19]- [22]. Studies have shown that the change of light intensity is closely related to the scale factor error and null shift [23]- [25].…”
Section: Introductionmentioning
confidence: 99%
“…At present, higher requirements are put forward for the accuracy of gyroscope at home and abroad, which is limited by the use environment, assembly process, manufacturing, material performance and other reasons. The main solution is to optimise the accuracy of the system and calculate effective compensation through the compensation technology and data pre-processing technology of computer software (Yang et al, 2021;Cheng et al, 2021;Tao et al, 2019). Different from the traditional gyroscope, laser gyro has the advantages of large measurement range, strong impact resistance and high precision, but it still has the problem of high economic cost.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the effectiveness of the two methods was proved by temperature error compensation tests. Tao and Li [19] analyzed the effect of high frequency oscillator voltage (UHFO) on the total reflection prisms laser gyro (TRPLG) bias. Moreover, a compensation method based on iteratively re-weighted least squares support vector machines (IR-LSSVM) was proposed, which can improve the TRPLG bias stability effectively.…”
Section: Introductionmentioning
confidence: 99%